The Influence of Self-Efficacy and Social Support on Interest in Attending Cross-Department Lectures - Nisa, Salsa; Firman, Firman; Hendra, Robi; Qudwatie, Muhammad; Muspawi, Mohamad (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2025)
This study aims to analyze the influence of self-efficacy and social support on students' interest in participating in cross-major courses in the Independent Student Exchange Program (PMM) at Jambi University. The approach used is ex post facto with the PLS-SEM method, using SmartPLS 3.2.9, and involving 110 students as respondents. The research instrument consists of 34 statements covering the variables of self-efficacy (X1), social support (X2), and student interest (Y). The analysis results show that self-efficacy and social support significantly affect student interest. The reliability and validity tests show that all constructs meet the standards with a Cronbach’s Alpha value above 0.9. These findings confirm that self-efficacy and social support play a crucial role in increasing students' interest in cross-departmental courses. Higher education institutions need to strengthen these two factors to increase student participation in interdisciplinary academic programs. Keywords: Self-efficacy; Social Support; Interest; Cross-Department Courses; Student Exchange; SmartPLS